PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDES): (Studi Kasus Kecamatan Parengan Kabupaten Tuban) - Ufid Nur Ufida; Adi Soesiantoro; Yusuf Hariyono (COMMUNITY OF RESEARCH LABORATORY SURABAYA)
Assessed factors. Particularly hampering the development of bum village is capital A limited one. Governance development, governance. Whether in government can Is done using some application of principles On the principles of good corporate-governance.(GCG) the purpose of this study. To know and analyze the differences in body development Village ventures. Bumdes) mojomreeds village with ngawun village District district district district district district district district district district district district, researchers using the research method Comparative qualitative. The data analysis techniques used in this studyWhich is model miles and huberman. The result is that the village of mojomalang Have not been able to apply the five GCG principles of transparency, accountability,Ideals, fairness, and response to the village of bumdes mojomalang Unorganized while bumdes ngawun could apply the 5 GCG principles Because it is organized.